Potensi Implementasi Teknologi Augmented Reality Pada Industri Food & Baverage Dalam Meningkatkan Kepuasan Pelanggan - Averil Rorizanda; Bambang Suharto (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
The dynamic and competitive Food and Beverage (F&B) industry requires continuous innovation to maintain its competitiveness. One innovation currently attracting attention is the use of Augmented Reality (AR) technology in the context of consumer experiences. With AR, customers can interact with menus, view 3D visuals of dishes, and access additional information. The implementation of AR in the food and beverage industry has the potential to significantly enhance customer satisfaction through improved customer experiences. This research aims to thoroughly explore the potential offered by Augmented Reality (AR) technology in enhancing customer satisfaction in the Food and Beverage (F&B) industry. By focusing on the integration of AR within the F&B environment, this study intends to understand how the implementation of AR can alter the way customers interact with products and services, as well as its impact on their perceptions and satisfaction, an area that currently lacks extensive research. The research methodology employed is a systematic literature review with a qualitative approach, enabling the identification, evaluation, and synthesis of findings from various related studies. The analysis of ten reviewed literature pieces indicates that the use of AR in restaurant menu applications holds significant potential for enhancing customer experiences and adding value to businesses in the F&B industry. Factors such as design, device availability, and consumer acceptance also play crucial roles in the successful implementation of AR in food and beverage businesses. Furthermore, companies need to pay attention to product quality, customer service, and competitive pricing to enhance customer satisfaction. Continuous monitoring of customer responses to the use of AR is also necessary for companies, as they should be prepared to make improvements or adjustments based on customer feedback.